ACSL4 as a Potential Target and Biomarker for Anticancer: From Molecular Mechanisms to Clinical Therapeutics - Hou, Jun; Jiang, Changqing; Wen, Xudong; Li, Chengming; Xiong, Shiqiang; Yue, Tian; Long, Pan; Shi, Jianyou; Zhang, Zhen (Frontiers in Pharmacology, 2022)
Cancer is a major public health problem around the world and the key leading cause of death in the world. It is well-known that glucolipid metabolism, immunoreaction, and growth/death pattern of cancer cells are markedly different from normal cells. Recently, acyl-CoA synthetase long-chain family 4 (ACSL4) is found be participated in the activation of long chain fatty acids metabolism, immune signaling transduction, and ferroptosis, which can be a promising potential target and biomarker for anticancer. Specifically, ACSL4 inhibits the progress of lung cancer, ER positive breast cancer, cervical cancer and the up-regulation of ACSL4 can improve the sensitivity of cancer cells to ferroptosis by enhancing the accumulation of lipid peroxidation products and lethal reactive oxygen species (ROS). However, it is undeniable that the high expression of ACSL4 in ER negative breast cancer, hepatocellular carcinoma, colorectal cancer, and Prostate cancer can also be related with tumor cell proliferation, migration and invasion. In the present review, we provide an update on understanding the controversial roles of ACSL4 in different cancer cells.